A rare case of high-grade synovial sarcoma of the hindfoot - Chiara Comisi; Tommaso Greco; Camillo Fulchignoni; Antonio Mascio; Francesco Farine; Elisa Troiano; Nicola Mondanelli; Giulio Menichini; Elisabetta Pataia; Giulio Maccauro; Carlo Perisano (Medicinski glasnik, 2025)
Aim: To report our personal experience in hindfoot reconstruction using an anterolateral thigh (ALT) free flap following radical resection of a high-grade synovial sarcoma. Methods: The patient underwent clinical and imaging assessments, and a biopsy of the lesion confirmed the diagnosis of synovial sarcoma (SS) of the hindfoot. A multidisciplinary team was involved to define the most appropriate therapeutic strategy. Results: After radical resection of the tumor mass, soft tissue coverage of the extensive skin defect was achieved using an ALT free flap. No local recurrences were observed during the follow-up period. At ap proximately twenty-four months after surgical treatment, the patient is able to ambulate independently, with no significant limitations in daily activities. Conclusion: The complex management of this rare disease requires a dedicated reference centre for foot and ankle surgery, supported by a multidisciplinary team including expert orthopaedic and plastic surgeons, as well as specialized oncologists, to ensure accurate diagnosis and appropriate treatment. Key words: flap, foot, limb salvage, reconstructive surgical procedures, soft tissue sarcoma
Keywords: flap; Foot; limb salvage; Reconstructive Surgical Procedures; Soft Tissue Sarcoma.